Eye Drawing with Gaze Estimation Model - Chiu, Po Chan; Yeo, Alvin Wee (Association for Computing Machinery, 2006)
Many research works in gaze-controlled interfaces have focused on target selection with eye gaze. For example, eye typing is built based on gaze patterns and language models. However only parts of these methods in target selection can be transferred to other domains. Unlike target selection in eye typing, eyedrawing target-selection is very small and the target could be less than 100 pixels target surface size. Overall, two kinds of eye drawing technique have already been proposed; a technique that applies free eye-paint [Tchalenko 2004; Gips and Olivieri 1996] and one that applies subtaskswitching between drawing and looking [Hornof et al. 2004]. The former is successful at inspiring creativity and selfexpression but cannot draw recognizable objects; and the latter is able to draw recognizable objects but cannot draw new objects in specific location on the screen.